Barriers to yoga therapy as an add-on treatment for schizophrenia in India - Baspure, Shubhangi (Medknow Publications & Media Pvt Ltd, 2012)
AIM: To describe the possible barriers to yoga therapy for patients with schizophrenia in India. MATERIALS AND METHODS: In a randomized control trial at NIMHANS, patients with schizophrenia (on stable doses of antipsychotics, 18–60 years of age, with a Clinical Global Impression-Severity score of 3 or more) were randomized into one of three limbs: Yoga therapy, physical exercise and waitlist. Of 857 patients screened, 392 (45.7%) patients were found eligible for the study. Among them, 223 (56.8%) declined to take part in the trial. The primary reasons for declining were analyzed. RESULTS: The primary reasons for declining were (a) distance from the center (n=83; 37.2%); (b) no one to accompany them for training (n=25; 11.2%); (c) busy work schedule (n=21, 9.4%); (d) unwilling to come for one month (n=11; 4.9%), (e) not willing for yoga therapy (n=9, 4.0%); (f) personal reasons (n=3, 1.3%); (g) religious reasons (n=1, 0.4%). In 70 patients (31.6%), no reasons were ascribed. No patient refused citing research nature of the intervention as a reason. CONCLUSION: More than half of the patients eligible for yoga did not consent to the study. Logistic factors, such as the need for daily training under supervision in a specialized center for long periods, are the most important barriers that prevent patients with schizophrenia from receiving yoga therapy. Alternative models/schedules that are patient-friendly must be explored to reach the benefit of yoga to patients with schizophrenia.